Exposure to the Layer with Steam Heat and Hot Water - Bobomurodov Utkir Ziyadullayevich (Scientific Trends, 2024)
In this traditional method, heat carriers of a calculated volume are driven through the driving wells for the effect of steam heat, thermal borders are formed, and unheated water is directed towards the well to be mined. In order to increase oil recovery in the productive layer, the properties of oil and water are absorbed at the expense of increasing the temperature by driving the heat carrier.